Markerless human motion tracking for golf swing application - Sim, Kwoh Fung (School of Mechatronic Engineering, 2011)
The main goal of this project is to develop a markerless human motion tracking system which is capable to perform motion tracking on a professional golfer while the individual is performing a full swing from a broadcast sports video.